Efektivitas Peran Guru Pendamping dalam Meningkatkan Kemandirian Belajar Matematika Siswa Autis di Sekolah Inklusi - Apriani Sutandi, Intan; Supardi (Zona Education Indonesia, 2025)
This study aims to determine the effectiveness of the role of accompanying teachers in increasing the independence of mathematics learning of autistic students in inclusive schools. The approach used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation. The research subjects consisted of accompanying teachers, classroom teachers, autistic students, and parents of students in one of the purposively selected inclusion elementary schools. The results of the study show that accompanying teachers play an important role in facilitating the understanding of mathematics material, forming independent learning habits, and increasing the confidence of autistic students. The strategies applied, such as graded prompting, task analysis, positive reinforcement, and the use of visual aids, have proven effective in encouraging students to be more independent in learning. In addition, collaboration between accompanying teachers, classroom teachers, and parents is the main supporting factor in an inclusive and sustainable learning process. In conclusion, the role of the accompanying teacher is very effective in increasing the independence of mathematics learning of autistic students, but the effectiveness is also influenced by the support of the school environment, cross-party coordination, and increasing the professional capacity of the accompanying teacher